Analisis Skenario Overload Shedding Pada Saat Pelimpahan Beban Gardu Induk 150kv Cilawu: Analysis of Overload Shedding Scenarios During Load Transfer at the 150 kV Cilawu Substation - Rosyidi, Rafsanjani Imam Akbar; Priatna , Edvin; Nurdiansyah, Rian (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2026)
The increasing demand for electrical energy, along with economic growth and regional development, requires power systems to have a high level of reliability. One of the common problems in power systems is the overload condition on power transformers, particularly during load transfers caused by faults or network maneuvers. If left unaddressed, overload conditions can cause excessive temperature rise, accelerate insulation degradation, and potentially lead to widespread blackouts. Therefore, a protection scheme in the form of overload shedding is necessary to maintain system continuity and reliability. This research aims to analyze overload shedding scenarios during load transfers at the 150 kV Cilawu Substation. The analysis was conducted to determine the condition of the power transformer under normal conditions, during fault conditions, and throughout the manual overload shedding process based on a load selection scheme. The research methods used include literature study, substation system data collection, network modeling, as well as load and load shedding simulations using ETAP 19.0.1 software and script-based MATLAB. The analysis focuses on static loading conditions without discussing transient effects and dynamic system stability. The results show that the implementation of the overload shedding scheme is capable of reducing the power transformer loading to within safe limits, thereby preventing transformer tripping and wider blackouts. Furthermore, proper load selection during the load shedding process plays a crucial role in maintaining the electricity supply to priority loads. Thus, the overload shedding scheme can be utilized as an operational strategy to improve power system reliability at the 150 kV Cilawu Substation.